To solve the inequality \(3x + 2 \geq 9 - 4x\), we can start by moving all terms involving \(x\) to one side and the constant terms to the other side:
-
Add \(4x\) to both sides: \[ 3x + 4x + 2 \geq 9 \] This simplifies to: \[ 7x + 2 \geq 9 \]
-
Next, subtract \(2\) from both sides: \[ 7x \geq 9 - 2 \] This simplifies to: \[ 7x \geq 7 \]
-
Finally, divide both sides by \(7\): \[ x \geq 1 \]
Thus, the solution to the inequality \(3x + 2 \geq 9 - 4x\) is: \[ x \geq 1 \]
The correct answer from the choices given is: x ≥ 1 (x greater-than-or-equal-to 1).